Familial motor neurone disease with dementia: phenotypic variation and cerebellar pathology. Issue 11 (14th November 2003) - Polvikoski, T M; Murray, A; Harper, P S; Neal, J W
Abstract : Objectives: To characterise the neuropathological phenotypes of two affected individuals from a family with an unusual clinical phenotype resembling motor neurone disease and dementia. Methods: Histological sections of cerebral cortex, basal ganglia, brain stem, cerebellum, and spinal cord were stained with haematoxylin-eosin, luxol fast blue, silver stains, anti-tau, anti-ubiquitin, anti-α-synuclein, and anti-neurofilament. Results: Numerous ubiquitin positive, tau and α-synuclein negative intraneuronal inclusions were present in the cerebral cortex (particularly within the dentate gyrus), cerebellar cortex, brain stem, and spinal cord. The cerebellar ubiquitinated inclusions were located in the proximal dendrite of the Purkinje cells. Loss of Purkinje cells and occasional silver and neurofilament positive axonal swellings (torpedoes) were also seen within the cerebellar cortex. The main difference between the two cases was the severity of the spinal cord involvement: no significant pathology was present within one, but obvious motor neurone disease within the other. Conclusions: The clinical and neuropathological findings in this family are best described as an example of familial motor neurone disease with dementia. Intraneuronal ubiquitin inclusions together with agyrophilic, neurofilament positive torpedoes were present within the cerebellar cortex, both previously unrecognised findings in this group of diseases.